The innovative moments coding system and the assimilation of problematic experiences scale: a case study comparing two methods to track change in psychotherapy - Gonçalves, Miguel M. (2014)
The Assimilation of Problematic Experiences Scale (APES) and the Innovative Moments Coding System were applied to transcripts of a successful case of linguistic therapy of evaluation independently by different research groups. Assimilation theory and research suggest that higher APES scores reflect therapeutic gains, with a level of approximately 4.0 separating good from poor outcome cases. The innovative moments (IMs) model suggests that IMs classified as reconceptualization and performing change occur mainly in good outcome cases, whereas action, reflection and protest occur in both good and poor outcome cases. Passages coded as reconceptualization and performing change were rare in this case, but 100% of them were rated at or above APES 4. By contrast, 63% passages coded as action, reflection or protest were rated below APES 4 (Chi-square = 28.62, p < .001). Implications for research are discussed.